Field monitoring on deformation of high rock slope during highway construction: A case study in Wenzhou, China - Ya-Qiong Wang; Shao-Bing Zhang; Long-Long Chen; Yong-Li Xie; Zhi-Feng Wang (International Journal of Distributed Sensor Networks)
In order to study the deformation stability of rock slope during the excavation of cutting slope and ensure the safety of rock slope during construction and operation period, this article analyzed the deformation law of a typical slope excavation by monitoring the surface deformation and the internal displacement of the rock mass. The surface deformation of the slope is monitored by setting monitoring points, and the internal deformation of the slope is monitored by installing multipoint displacement meters and inclinometers. Therefore, the relationship between slope excavation and deformation is obtained. The analysis of monitoring results shows that the slope is stable before excavation, and the displacement of the slope is gradually increased with the slope excavation. After the excavation, the displacement of each slope tends to converge. The maximum displacement in surface monitoring points is 12.30 mm, and the displacement parallels to the direction of the expressway. The maximum vertical displacement in surface monitoring points is 10.60 mm which occurred in the third step; the maximum internal displacement is 11.02 mm which mainly occurs in the weak structural plane of the rock boundary. During the excavation of the weak rock slope, the slope rock mass is prone to large displacement deformation. After the excavation, the slope surface displacement and internal displacement tend to converge in a short time.